Cultural Adaptation of Child Discipline Measures for Puerto Rican Mothers: Enhancing the Cultural Sensitivity of Parenting Assessments - Jahaira Capellán; Hugh F. Crean; Susan W. Groth; Maria Quiñones-Cordero; José G. Pérez-Ramos; Hyekyun Rhee (MDPI AG, 2024)
Background/Objectives: Puerto Ricans (PRs) face significant challenges in accessing essential parenting resources and support due to language barriers and lack of culturally appropriate healthcare services, perpetuating health disparities. Cultural adaptation of psychosocial measurement tools is crucial for promoting health equity and improving health outcomes. This study describes the cultural adaptation of two parenting discipline assessment measures for use with Spanish-speaking PR mothers of 2-4-year-old children. Methods: We used a community-engaged, mixed-methods approach to measurement adaptation that involved independent translations (n = 2), back-translations (n = 2), and an adaptation committee (n = 6, including all translators) who reviewed, appraised, and modified survey versions. We conducted cognitive interviews (n = 20) to pretest the semi-finalized Spanish measures and assess mothers' understanding of survey items. Results: Mothers had a mean age of 28.6 years. Most were married/cohabitating (70%), had a high school diploma or GED (90%), and a household income of less than $40,000 (68%). Indexed children's mean age was 2.9 years, with most identified by mothers as female (60%). Feedback from the adaptation committee and pretesting participants led to specific changes like rephrasing culturally specific terms and adjusting examples to better fit the daily experiences of PR mothers. Most mothers found the Spanish version of the measures to be clear and culturally relevant. This cultural adaptation process addressed translation inconsistencies and design issues, and better captured culturally relevant discipline practices. Conclusions: Engaging communities in measurement adaptations ensures culturally and linguistically tailored measures that respect participant preferences, strengthen partnerships, and enable interventions to address health disparities, thereby promoting child health.